Endangered species and endangered knowledge - Dubois, Alain (Zootaxa, 2009)
The recent discovery of a new species of land iguana in the Galapagos (Tzika et al. 2008; Gentile et al. 2009; Gentile & Snell 2009) is indeed an exciting novelty, of great interest to all zoologists and evolutionary biologists. This species being apparently represented only by a very small population with a very limited range, it was described as a new taxon following an unusual procedure: no fixed specimen(s) (holotype or syntypes) was deposited in a permanent collection, but a live specimen, in which a transponder had been inserted and which then had been released, was designated as holotype. As analysed in detail by Dubois & Nemésio (2007), because of the unclear wording of Art. 16.4.2 of the Code, whether such a nomen is nomenclaturally available is open to question, and pending a clarification of the published Rules of the Code, will remain so. In this context, some comments on the paper by Gentile & Smell (2009), from a taxonomic and nomenclatural point of view, are in order. I thank Zhi-Qiang Zhang, Chief Editor of Zootaxa, for inviting me to contribute to this discussion.